Model Shuttle Flow Dalam Pembelajaran Integratif Holistik Bahasa Indonesia Di Sekolah Dasar - Sudirman, Sudirman (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2021)
This paper is an innovative concept in the field of learning, especially Indonesian in elementary schools. The Shuttle Flow Model is an invention, the result of contemplating experiences during and after teaching, observing, and training teachers in learning practices. The existence of a ‘shuttling’ movement between values and competencies during learning and prioritizing the elements of connectedness, wholeness, and beingness are the main features of this model. The purpose of this model is to help teachers teach Indonesian in an integrative-holistic manner as well as a solution to teacher constraints in integrative learning in primary schools. This model displays the flexibility in integrating the four aspects of language skills with the core competencies in the 2013 Curriculum which flow back and forth in the direction formed by the flow of competencies. This direction shows the relationship between aspects of language skills from and to core competencies. That is why it is called the Shuttle Flow Modle or the Shuttle Flow Model. The presence of this model is so important to guide teachers in developing the self-potential of students holistically. By using this model, teachers will never run out of material in teaching, they can even find out what aspects and competencies the students are weak in. There are five strengths of this model and four weaknesses. Strengths are intensified to minimize weaknesses. It is recommended that this learning model be an innovative choice in learning in elementary schools.